Mechanisms and applications of natural plant ingredients in modulating amino acid metabolism for the improvement of diabetic retinopathy: a review - Zhang, Le-yi; Zhang, Tian-yi; Zheng, Ya-juan; Li, Jia-xin; Chen, Hu-rong; Cao, Jing; Dan, Teng (Frontiers in Endocrinology, 2026)
Diabetic Retinopathy (DR) is a leading cause of vision loss in diabetic patients, driven by oxidative stress, inflammation, and vascular abnormalities. Recent studies highlight amino acid metabolism abnormalities, particularly in glutamate, arginine, and tryptophan, as critical factors in DR pathogenesis. Preclinical evidence suggests that these metabolic disturbances may contribute to retinal neurodegeneration and vascular damage, offering potential new targets for therapy. Natural plant-derived compounds, such as flavonoids, catechins, and alkaloids, have been shown in animal and cell culture studies to regulate amino acid metabolism and may offer therapeutic potential for DR, although clinical validation remains limited. These compounds exhibit antioxidant, anti-inflammatory, and neuroprotective properties. Flavonoids improve amino acid accumulation, reduce oxidative stress, and protect retinal cells, while catechins enhance amino acid synthesis and redox balance. Alkaloids like berberine regulate nitric oxide synthesis, improving retinal microcirculation and endothelial function. In DR, glutamate excess activates NMDA receptors, leading to retinal neuronal toxicity, while arginine and tryptophan metabolism abnormalities further disrupt vascular and immune function. Natural drugs targeting these pathways could alleviate oxidative stress, inflammation, and retinal damage. However, challenges remain in clinical application, including low bioavailability and variability in product quality. Future research should focus on multi-omics integration, personalized medicine, and clinical trials to establish robust evidence for the use of natural drugs in DR treatment, ultimately improving long-term visual outcomes and quality of life.